Transient Acute Myeloid Leukemia in a Newborn with Downs Syndrome - Haque, Zabrul SM; Jahan, Nasim; Raha, Biplob Kumar; Hassan, Mahmuda; Begum, Mariam; Rob, AWS; Yasmin, Sabina; Hasnat, SKA; Farhana, Tasnim (Journal of Bangladesh College of Physicians and Surgeons, 2017)
We report the case of a newborn with Down's syndrome associated with transient acute myeloid leukemia (AML). The leukemic presentation resolved spontaneously without treatment just 4 weeks after birth. A 2 days old newborn presented with respiratory distress, lethargy, poor suck and mild hepatosplenomegaly with features of Down's syndrome. Total white cell count was 144,000/cmm with blasts 92%. Other Septic work up was negative. Peripheral blood smear revealed hyper leukocytosis and presence of blast cells. Flow cytometric analysis revealed acute myeloid leukemia. The peripheral blast cells persisted for 4 weeks, after which the hemogram and the differential WBC count returned to normal and a final diagnosis of transient acute myeloid leukemia was made. Only few cases of congenital leukemia with Down's syndrome have been reported in the literature. In Down's syndrome, AML whether transient or not, generally shows cytogenetic and molecular aspects that differ from those of adult acute leukemias J Bangladesh Coll Phys Surg 2016; 34(4): 213-217